FAKTOR-FAKTOR YANG BERPERAN DALAM MUNCULNYA RESISTANCE TO CHANGE TERHADAP PENERAPAN E-LEARNING (STUDI KASUS DI SMU MUHAMMADIYAH 2 YOGYAKARTA) - , VISKA ARMALINA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
E-learning is an alternative to transfer information effectively and efficiently in adopting information technology as a medium of teaching and learning. Information technology applied must be Acceptable, if it's not, so there will be a behavior of resistance to change (Resistance to change). SMU Muhammadiyah 2 Yogyakarta is one of the main international-based high school that is still in the pioneering stages of e-Learning. School facilities and infrastructure is considered to be eligible for the implementation of e-Learning as a whole, but in a fact, e-learning has not fully implemented in SMU Muhammadiyah 2 Yogyakarta. This research has a purpose to determine the dominant factor which influence the emergence of resistance to change towards the implementation of e-learning in educational institutions. This research uses the Human Centered Approach methods that related with Resistance to change in arranging of its questionnaire instrument and using factor analysis in data processing and analysis. The process of taking samples using simple random sampling technique in which the taking of samples of the population that was randomly without regard to strata that exist in the population. Model of factor analysis used is Principal Component Analysis (PCA). Phases of factor analysis such as the correlation matrix, factor extraction, factor rotation, and interpretation of factors. Based on the results of factor analysis that has been done, then the factors that influence in the emergence of resistance to change in sequence from the most dominant are the Competence Factor with the percentage value of variance 39.431%, Factor of motivation and implementation planning with the percentage value of variance 11.977% , Factor of communication with the leader with the percentage value of variance 7.383% , Factor of Cultures with the percentage value of variance 5.478%, Factor of situation and condition with the percentage value of variance 5.048% , Personality Factor with the percentage of variance 4.318%, and the Security factor with the percentage value of variance 3.925% . It would be better if take the sampling is not only teachers but also involves students and mapped based on spesific criteria which are equipped with the characteristics of each sample.